2017
DOI: 10.2174/1573397111666151026223501
|View full text |Cite
|
Sign up to set email alerts
|

No Zinc Deficiency But a Putative Immunosuppressive Role for Labile Zn in Patients with Systemic Autoimmune Disease

Abstract: There is no evidence of Zn deficiency in patients with pSS or SLE. Labile Zn levels are unexpectedly high in SLE patients, independent of cytokine levels and may play a role in immune modulation through increased NK numbers and autoantibody containment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Other studies reported similar results 47 , 48 . However, some studies did not observe a significant difference in serum Zn concentrations between SLE patients and healthy controls which is similar to the finding of the present study 49 , 50 .…”
Section: Discussionsupporting
confidence: 92%
“…Other studies reported similar results 47 , 48 . However, some studies did not observe a significant difference in serum Zn concentrations between SLE patients and healthy controls which is similar to the finding of the present study 49 , 50 .…”
Section: Discussionsupporting
confidence: 92%
“…This is especially important regarding autoimmune diseases, since a number of them are associated with disturbed zinc homeostasis, such as rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, and colitis [ 4 , 42 , 43 , 44 ]. Since T cell maturation, differentiation, and function is reliant on adequate zinc status [ 32 , 45 , 46 ], this connection is likely to be one reason for the development or progression of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, contrary to the above evidence, Nossent et al showed that labile zinc levels are unexpectedly high in patients with autoimmune diseases and they also suggested that zinc may be probably causing an immunosuppressive effect in these patients. [58] Hence, the exact mechanism by which zinc acts as an immunomodulator remains unclear.…”
Section: Lichen Planus (Loe 1 B)mentioning
confidence: 99%